(untitled) (International Journal of Nursing Education, 2019)
Low back pain is the second leading health problem concerning disability and visits to the doctors in population under 45 years of age. Musculoskeletal system disorders including LBP comprise significant occupational injuries and disability within nursing profession. LBP is reportedly the most important reason for nurses’ decision to change their job. In terms of high risk groups for occupational low back pain, the, nurses and other health workers are considered to the highest incidence of low back pain requiring medical and hospital intervention. Nursing staffs have one of the highest incidences of work-related back problems of all occupations. The incidence rates continue to climb and the direct and indirect costs associated with back injuries for nurses are estimated to be 20 billion annually The objectives was to assess the knowledge of staff nurses regarding proper body mechanics in prevention of low back pain before giving the selfinstructional module and to determine the effectiveness of self-instructional module regarding knowledge on proper body mechanics in prevention of low back pain among staff nurses. One group pre test- post-test research design was selected for the study. 60 samples were selected by using purposive and convenience sampling technique. Samples were selected from medicine, surgery and orthopedic ward of Pradyumna Bal memorial Hospital, Bhubaneswar Odisha. After obtaining the written consent from the 60 staff nurses to participate in this study, the knowledge was assessed using a self administered structured questionnaire. After completing the pre test, a Self Instructional Module on correct body mechanics in prevention of low back pain was given to them and the post test was done after 7 days. The data thus collected was analyzed using descriptive and inferential statistics. The study findings interpreted that in orthopedic ward out of 20 staff nurses, (45 %) have good knowledge, (5 % )have average knowledge & (50 % ) have poor knowledge of prevention of low back pain, in surgery ward out of 20 staff nurses (60 %) have good knowledge,(25 %) staff nurses have average & (15 % ) staff nurses have poor knowledge and in medicine ward out of 20 staff nurses, (70%) have good,(30 %) have average knowledge & none of the staff nurses have poor knowledge on prevention of low back pain. The study findings showed that self-instructional module was effective in improving knowledge of staff nurses